(untitled) (Journal of Hama University, 2022)
The Aim Of The Research Is To Identify The Level Of Positive Interaction With Life scripts, And The Level Of Emotional Awareness And Its Dimensions Among The Sample. It Also Sought To Reveal The Relationship Between Life scripts And Emotional Awareness. To Achieve These Goals, The Mcneel Scale (Mcneel, 2010) Was Used for injunctions, And The Emotional Awareness Scale Prepared By The Researcher. And Its Application To The Research Sample Consisting Of (115) Adults, Their Ages Ranged Between (22-50) Years. The Researcher Used The Descriptive Analytical Method To get Results That Showed That The Level Of Positive Interaction On The Life scripts Scale and Emotional Awareness Scale are Higher Than The Average. The Results Also Showed A Significant Relationship Between Life scripts And Emotional Awareness And Its Dimensions. The Researcher Recommended The Importance Of Providing The Rest Of The Society With Methods Of Positive Dealing With scripts Through Psychological Programs, Due To Its Role In Improving Positive Interaction With Emotions As Well.